Protective effects of vitamin e against bisphenol-induced toxicity in porcine spermatozoa in vitro - Khanh Duy, Nguyen Lam; Tai Nguyen, Cao Thi; Gia Han, Nguyen Hoang; Thanh Khuong, Tran Thi (Academia Journal of Biology, 2025)
Bisphenol A (BPA) is a toxic compound that negatively impacts reproductive function, particularly affecting male gametes. Vitamin E, a potent antioxidant, is known for its ability to neutralize reactive oxygen species. This study aimed to further elucidate the toxic effects of BPA and the protective effects of vitamin E on sperm quality through in vitro experiments using porcine sperm. In the first experiment, sperm samples were exposed to BPA concentrations of 0 µM, 1 µM, 10 µM, and 100 µM for 1, 2, and 4 hours. In the second experiment, sperm samples were treated with 0 µM or 100 µM BPA, or 100 µM BPA combined with 200 µM vitamin E for 1 hour. Results showed a time- and dose-dependent decline in sperm quality with increasing BPA exposure. Notably, the 100 µM BPA concentration caused the most severe sperm inactivation at all time points. However, the co-treatment of 100 µM BPA with 200 µM vitamin E significantly mitigated BPA’s toxic effects. After 1 hour of co-treatment, porcine sperm exhibited improved overall motility, progressive motility, viability, antioxidant capacity, and reduced DNA fragmentation rates, with values of 87.39%, 92.42%, 74.83%, and 11.61%, respectively. These findings demonstrate both the detrimental effects of BPA and the protective role of vitamin E in maintaining sperm quality.